IMPLEMENTATION OF SCIENTIFIC-BASED PROBLEM SOLVING LEARNING TO INCREASE STUDENT LEARNING OUTCOMES IN REACTION RATE MATERIALS IN CLASS XI MIPA 3 SMA NEGERI 1 BANGSAL - Alim Efendy (Jurnal Scientia, 2022)
The results of initial observations in class XI MIPA 3 SMA Negeri 1 Bangsal showed more than 50% of students were not complete in learning the reaction rate material. The low learning outcomes are due to the application of learning methods that are not suitable, students are passive in learning, there is no assessment of assignments. The purpose of this study was to analyze the improvement of learning outcomes for class XI MIPA 3 SMA Negeri 1 Bangsal through the application of scientific-based problem solving methods. To improve student learning outcomes on the reaction rate material, a class action research was conducted which consisted of two cycles. Each cycle consists of stages of planning, implementation, observation and reflection. Based on the results and discussion, it can be seen that learning using problem solving provides convenience for teachers in learning, makes learning student-centered, completes learning outcomes, and can teach and train students' character behaviors. The implementation of the lesson plans was categorized as good with an average score of 3.09 in the first cycle and 3.27 in the second cycle. Student activity reached 85.26% in the first cycle and increased to 92.22%. In the aspect of scientific behavior, both cycles show that they are in the good category. Mastery learning outcomes also showed an increase, from 74.3% in the first cycle to 94.3% in the second cycle.